Penyelesaian Tindak pidana Ringan melalui Restorative Justice Conferencing Initiative - Noya, Ekberth Vallen; Walakutty, Ade (SANISA: Jurnal Kreativitas Mahasiswa Hukum, 2024)
Introduction: Indonesia is a country that upholds the law, so Indonesia is called a country of law. This is clearly stated in Article 1 paragraph (3) of the 1945 Constitution of the Republic of Indonesia, the formulation of which is "The State of Indonesia is a state of law". Legal/legitimate law. Therefore, everything in Indonesia is regulated by law, one of which is criminal law. Criminal law is the law that regulates violations and crimes against the public interest, actions which are threatened with punishment if someone suffers or sends a message.Purposes of the Research: To carry out a law reform to become a better IndonesiaMethods of the Research: This type of research is normative, namely doctrinal legal research or theoretical legal research. It is called normative legal research because what is studied is law from a theoretical or normative aspect, not to examine the applied or implementation aspects. The approach used is philosophical.Results of the Research: Restorative Conferencing Initiatives are not new in Indonesia. Long before this country became independent, indigenous community groups had resolved legal problems using Restorative Conferencing Initiatives. It's just that in order to name it according to developments in the legal world, we are familiar with the term Restorative Conferencing Initiatives. The resolution process varies, according to the prevailing habits and social system in that community group. The implementation of the restorative conference initiative in Indonesia has started at the family level of indigenous groups and other social environments. The position of the restorative conference initiative is at the pre-adjudication stage and involves victims of perpetrators and parties who feel disadvantaged in an indigenous community group. The important role of families and community leaders is needed in this resolution process.